Taxonomic mapping of Tabanidae (Diptera: Tabanidae) from Darjeeling Himalaya, a part of Indo-Burmese biodiversity hotspot. (2nd January 2017) - Maity, Aniruddha; Naskar, Atanu; Hazra, Surajit; Sengupta, Jayita; Parui, Panchanan; Banerjee, Dhriti
Abstract: The family Tabanidae includes horse flies (referred to flies of genus Tabanus ), deer flies ( Chrysops ) and clegs ( Haematopota ). They are mainly popular in this tropical climate for their disease-causing abilities and one of those important disease that even may lead to fatal consequences in cattle animals is Surra disease that causes havoc in wild and livestocks in this region. A total of 22 tabanid species under 5 genera, 4 tribes and 3 subfamilies so far known from Darjeeling district of West Bengal, are keyed and diagnosed. Their distribution patterns are discussed wherever deemed necessary. Among them, single genus namely Hybomitra Enderlein, 1922 and four species are reported for the first time from this district and also from the state of West Bengal. Moreover, there is scope for taxonomic studies on this group of flies in this important biodiversity hot spot of northeastern Himalaya since it falls under diverse Indo-Malayan biome. Most of the species are however expected to exhibit extensive distribution pattern in the long run, as more extensive taxonomic and ecological studies are due on this interesting group of biting flies of veterinary importance.